The growth of flue-cured tobacco in acid soils - Ryding, William Wallace (Rhodes University, Faculty of Science, Department of Chemistry, 1969)
The main effects of lime, aluminium, iron and manganese were studied in field and greenhouse grown tobacco; relations between soil and plant measurements were examined. Ground limestone, ground mixed lime, ground dolomite and slaked lime at rates equivalent to 1,000 and 2,000 lb. CaC0₃/acre increased yield and quality of flue-cured tobacco both on Triassic and granite sands, whether applied early (February/March) or late (September); the highest rate and late application were often best. Yields increased with 4,000 and 6,000 lb. dolomite/acre applied late, but quality decreased when the pH was about 6.0. Lime did not affect leaf maturity as reflected by nitrogen and reducing sugars concentration . Where leaf discolouration (slate) occurred, the best quality and least discoloured leaf had the lowest manganese concentration and was grown on limed soil. On a very acid and probably nitrogen deficient soil, lime, borax and nitrogen (nitrate only tested) reduced the discolouration and improved the quality, but potassium sulphate increased discolouration and decreased quality. Calcium concentration in the leaf was increased by lime, particularly calcitic materials, and magnesium concentration was increased by dolomite. Lime also increased the filling value and petroleum ether extract, but decreased manganese, boron, chloride and sometimes potassium, and had no effect on phosphorus, nitrogen, aluminium, iron, crude fibre, nicotine, reducing sugars and equilibrium moisture. The inorganic composition of greenhouse plants was similar; generally gypsum increased calcium concentration more than calcium carbonate but it did not affect manganese concentration, which was decreased by calcium carbonate. In the stem and roots of field grown plants (dolomite only tested), the concentration of magnesium was increased but the concentrations of calcium, potassium, aluminium and iron were unaffected. Although the concentration of nitrogen was increased and that of phosphorus was decreased in the stem, these were unaffected in the roots. Aluminium and iron behaved differently to other nutrient ions, being more concentrated in the roots than aerial plant parts. Boron and magnesium deficiencies were observed in a dry and wet year, respectively, suggesting that variable mineral deficiencies can affect responses to lime. Initially soil pH was affected more by source of lime, but later mostly by rates. Slaked lime increased the soil pH more than did ground limestone, mixed lime or dolomite. In a glasshouse experiment, pH was more important than calcium supply and in the field, the largest yields were often associated with the highest pH. In pot experiments, aluminium drastically reduced yields in nutrient solution but not in soils, whereas iron was more severe in soils; manganese had little effect on yield. Manganese was readily taken up and translocated to the tops, but aluminium and iron were mainly concentrated in the roots, as was found in field grown plants. Iron decreased manganese concentration in all plant parts and aluminium decreased calcium and manganese in nutrient solution only. Although aluminium and iron generally increased the concentration of phosphorus in the roots, they did not interfere with phosphorus transport in the plant. Manganese caused the leaf to become chlorotic and when no iron was present the upper leaves became yellow, and developed brown and white lesions. However, in soil grown plants, sufficient iron was present in the soil solution to prevent break down of tissue. Yellowing of the upper leaves also occurred when plants were grown in nutrient solution with aluminium and no iron; when both were present, the plants were darker in colour. Although aluminium damaged roots in nutrient solution, high rates of iron severely damaged leaves of plants grown in soil. Since the concentrations of aluminium, iron and manganese were decreased in the soil solution by liming, they were compared with plant growth and composition in 17 different soils, with and without lime. As was expected, lime increased soil pH. It also increased exchangeable calcium, but decreased exchangeable aluminium, iron and manganese; exchangeable magnesium and potassium and resin extractable phosphorus were not affected. As the Ratio Law does not hold for all Rhodesian soils, anion adsorption will be avoided if the soils are equilibrated with O.OOOSM CaC1₂; the concentrations of the cations in solution were affected in the same way as exchangeable cations, but phosphorus was increased. There was no relationship between yield of tobacco and its chemical composition. The correlations between soil solution data and plant composition were poor, except for manganese and phosphorus; the relation between Mn ppm. in plant vsa (superscript)Mn/a (superscript)Ca + Mg (enclosed in square root sign √) in solution, and P% vs pH₂ P0₄ or pH₂ P0₄ +½ pCa, were both curvilinear. On the other hand, all measurements of exchangeable cations were poorly correlated with plant composition. Finally yield was poorly correlated with soil solution data, and pH was as satisfactory as any other measurement tested. Manganese toxicity was observed on three soils, and a probable manganese deficiency on one. It was not possible to define a limit above which manganese toxicity occurred, but manganese deficiency developed at about 63 ppm. manganese. Variations in pH and the availability of aluminium, iron and manganese occurred when soils were incubated at about field capacity, generally the main effects having developed within seven days. In all soils, there was an initial increase in soil pH and a maximum value was reached in one to four days, decreasing by variable amounts with longer periods of incubation. Although the concentration of aluminium was larger than that of iron, the relation between both ions and soil pH was curvilinear, their concentrations increasing with decreasing pH. Increased temperature of incubation increased pH with a resultant decrease in the concentration of aluminium, but in one soil it appreciably increased the availability of iron in the early periods of incubation. Autumn and spring ploughing did not affect subsequent pH or the concentration of aluminium and iron in the soil solution. Manganese concentration varied from soil to soil and was not related to soil pH. In most soils there was a decrease in manganese concentration with length of incubation and it decreased more rapidly the lower the initial concentration. Temperature effects were variable and moisture affected the behaviour of manganese more than temperature. These findings and the distribution of aluminium, iron and manganese in the plant helped to explain the poor correlations.
Keywords: Flue-cured tobacco -- Zimbabwe; Acid soils -- Zimbabwe